Potencialidades e implicações do olhar no Livro do desassossego de Fernando Pessoa - Marques, Julia Medrado (2019)
This work aims to develop a reading of the potentialities and implications of the gaze and its image captures in Livro do desassossego, an unfinished work in prose by the Portuguese writer Fernando Pessoa (1888-1935). For this, four reading keys are privileged from the punctual analysis of excerpts of fragments in which one can highlight the vision of: a) windows and landscapes; b) photographs; c) oil and artificial figures and d) furniture, objects and minimal things. Because it is a posthumous work whose editions can be read as apocryphal attempts, even the choice of corpus is problematized, since there is no definition as to its best organization. The first chapter thus presents the work’s state of the art, its point of view, and reviews the heteronomy of its different phases. In search of interpretative ways, it also analyzes the refusal of action and its referral to the contemplative exercise. Philosophical and psychoanalytic biases are proposed to help the analysis of the narrator's gaze in the work. The second chapter is based on the approach to the theories of the philosopher José Gil (1987) on the metaphysics of senses and sensations; on the literary analyzes of Paulo de Medeiros (2015) and on the theories of the look and its double distance of the philosopher Georges Didi-Huberman (2010). The fragments of the Book that make a clear reference to the eye are highlighted, in which probable potentialities, implications, references, associations, deviations, deductions or inferences are pointed out. The third chapter discusses the potentialities and implications (ontological, metaphysical, dialectical, sensorial) in order to contribute to broaden the field of analysis of the senses in (and of) the work. This is a qualitative research of basic, exploratory and descriptive nature, and uses analytical and hypothetical-deductive methods